Radon and uranium concentrations in drinking water sources along the fault line passing through Reasi district, lesser Himalayas of Jammu and Kashmir State, India. Issue 7 (3rd October 2017) - Kumar, Ajay; Vij, Raman; Sarin, Amit; Kanwar, Priya
ABSTRACT: The presence of radon in drinking water causes radiation-related health hazards both through inhalation and ingestion. In the present study, 28 drinking water samples from natural flowing springs, freshwater ponds, and deep hand pumps were analyzed in the fault zone of Reasi region of Jammu & Kashmir. Radon measurement was performed using the RAD7 electronic device for radon content determination. Average mean values of these samples vary from 2.80 ± 0.78 to 74.37 ± 2.76 Bq l −1 . Nineteen drinking water samples analyzed have radon levels in excess of USEPA recommended maximum contamination level of 11.1 Bq l −1 . The annual effective dose from radon in water due to its ingestion and inhalation per individual has also been calculated. Uranium concentration in these water samples was also analyzed for a possible correlation between different types of rocks and values of radon in water. Results obtained have been compared with the results of earlier investigators for mean radon concentration and mean annual effective dose for radon in water from different regions of northern India and Pakistan. It has been found that radon levels in a significant number of water samples collected from the region of fault line are higher than USEPA recommendations. A positive correlation is observed between the depth of the water source and the values of radon levels in water samples collected from these sources. Measurements of radon concentration in these water samples were also performed with a Smart Radon Monitor designed by Bhabha Atomic Research Centre, Trombay, Mumbai, India, for a comparative analysis.